2017
DOI: 10.1016/j.neulet.2017.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Global motion perception is associated with motor function in 2-year-old children

Abstract: The dorsal visual processing stream that includes V1, motion sensitive area V5 and the posterior parietal lobe, supports visually guided motor function. Two recent studies have reported associations between global motion perception, a behavioural measure of processing in V5, and motor function in pre-school and school aged children. This indicates a relationship between visual and motor development and also supports the use of global motion perception to assess overall dorsal stream function in studies of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
(42 reference statements)
5
16
0
Order By: Relevance
“…Toddlers with slow gross motor development had a greater tendency of exophoria and a further near point of convergence (NPC) than toddlers with fast gross motor development. These findings agree with previous studies that demonstrated the link among the visual and motor systems in babies, toddlers, and children [4,[13][14][15][16][17]19,21,[24][25][26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Toddlers with slow gross motor development had a greater tendency of exophoria and a further near point of convergence (NPC) than toddlers with fast gross motor development. These findings agree with previous studies that demonstrated the link among the visual and motor systems in babies, toddlers, and children [4,[13][14][15][16][17]19,21,[24][25][26].…”
Section: Discussionsupporting
confidence: 93%
“…Their results demonstrated that global perception of movement and binocular vision are associated with motor function at an early stage of development as measured by the Bayley Scale of Infant and Toddler Development 3rd edition (BSID-III). All of the scientific literature reviewed included babies and toddlers [12,[22][23][24] with some form of visual impairment or born with risk factors for neurological development [25,26]. To the best of our knowledge, this is the first report to study visual and motor development in a sample of between two and three-year-olds both visually and from the perspective of motor development.…”
Section: Introductionmentioning
confidence: 99%
“…The observed association between GMP and language ability is in line with previous research that showed concurrent links between GMP and verbal ability in 2-and 4.5-year-old children (Chakraborty et al, 2017;Thompson et al, 2017). The present findings add to the literature by demonstrating for the first time that early GMP may also be associated with later language ability.…”
Section: Discussionsupporting
confidence: 92%
“…The development of visual and motor systems is closely related [29], and coordination of visual-motor function is thought to occur within the ventral and dorsal cortical visual streams. The ventral stream supports form processing and object recognition, and includes the occipital primary visual cortex and the inferior temporal lobe.…”
Section: Discussionmentioning
confidence: 99%